Pengaruh Bukti Fisik, Kehandalan dan Jaminan terhadap Kepuasan Konsumen dalam Penggunaan Digital Payment Dana pada Mahasiswa FEB UM Metro - Yusman, Al'Rafi Fulqi; Yateno, Yateno (Jurnal Manajemen DIVERSIFIKASI, 2021)
The development of information and communication technology makes all human activities easier, both in the economic and social The survey method was chosen as the primary data source. The survey method focuses on collecting data on respondents who have certain information, allowing researchers to solve problems. In this study, the population was FEB students of Muhammadiyah Metro University. The sampling technique used accidental sampling with a sample size of 75 people. The results showed that : there is a positive and significant influence between physical evidence on customer satisfaction in the use of funds in the February metro, there is a positive and significant influence between reliability on customer satisfaction in the use of funds in the Metro Metro, there is a positive and significant influence between guarantees on customer satisfaction in the use of funds in the Metro Metro, and there is a positive and significant influence between (physical evidence, reliability and assurance) simultaneously on customer satisfaction in the use of funds in the metro February.